The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s11051-019-4651-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation exposure to various nanoparticles in work environment—contextual information and results of measurements

Abstract: Outside the wide range of potential benefits, the use of nanomaterials can endanger human health, mostly through skin contact and the risk of inhalation. This article presents the results of harmonized measurements with contextual information on the emission of nanoparticles during the manufacturing and application of nanotechnology products. The purpose of the research was to investigate the actual levels of exposure to nano-objects in real working conditions in chosen Polish companies. Measurements were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…The National Institute for Occupational Safety and Health (NIOSH) has recommended the general exposure limits of 0.3 mg/m 3 of air for the nano form of TiO 2 [114]. According to the review presented by NIOSH, five epidemiological studies have already been carried out on the TiO 2 NPs exposure of workers, which showed no relation between TiO 2 NPs and the mortality or morbidity from lung cancer.…”
Section: Titanium Dioxide Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Institute for Occupational Safety and Health (NIOSH) has recommended the general exposure limits of 0.3 mg/m 3 of air for the nano form of TiO 2 [114]. According to the review presented by NIOSH, five epidemiological studies have already been carried out on the TiO 2 NPs exposure of workers, which showed no relation between TiO 2 NPs and the mortality or morbidity from lung cancer.…”
Section: Titanium Dioxide Nanoparticlesmentioning
confidence: 99%
“…Thus, NIOSH have considered that there is insufficient evidence to classify TiO 2 NPs as potential carcinogens in an occupational context. However, according to the classification of the International Agency for Research on Cancer (IARC), TiO 2 NPs are considered as "possibly carcinogenic to humans"; since TiO 2 NPs have shown carcinogenic effects and genotoxicity in animals, its genotoxic potential has also confirmed [114,115]. Moreover, present in vitro tests using bacteria have not proved genotoxicity induced by titanium dioxide, while the positive effects have been reported in eukaryotic cells and in animals [116].…”
Section: Titanium Dioxide Nanoparticlesmentioning
confidence: 99%
“…In occupational industrial settings, efforts to evaluate environmental health and safety implications of UFP are frequently based on physical particle properties such as particle number concentration or size distribution ( Gonzalez-Pech et al , 2019 ; Oberbek et al , 2019 ; among others). When referring to engineered nanomaterials (ENMs), the body of literature reporting physical properties is large ( Maynard et al , 2004 ; Maynard and Aitken, 2007 ; Hämeri et al , 2009 ; Kuhlbusch et al , 2011 ; Brouwer et al , 2012 ; Hristozov et al , 2012 ; Falk et al , 2016 ; among many others).…”
Section: Introductionmentioning
confidence: 99%
“…These nanosized dusts existing in mining environment throw into a question that the current OELs in assessing dust hazard using a mass concentration instead of a number concentration. Because the total mass of the nanoparticles contained in the aerosol may constitute only its percentage, but their number can reach over 80% of the total particles (Oberbek 2019). A better understanding of the formation, transformation, and adverse health impacts of nano-scale dusts would contribute to the protection of miners' health and future regulation formulation.…”
Section: Gravimetric Methodsmentioning
confidence: 99%